Thermodynamic and structural characterization of high-entropy garnet electrolytes for all-solid-state battery - Ting, Yin-Ying; Ye, Ruijie; Dashjav, Enkhtsetseg; Ma, Qianli; Taminato, Sou; Mori, Daisuke; Imanishi, Nobuyuki; Finsterbusch, Martin; Eikerling, Michael H.; Guillon, Olivier; Kaghazchi, Payam; Kowalski, Piotr M. (Frontiers in Energy Research, 2024)
This study explores multi-component garnet-based materials as solid electrolytes for all-solid-state lithium batteries. Through a combination of computational and experimental approaches, we investigate the thermodynamic and structural properties of lithium lanthanum zirconium oxide garnets doped with various elements. Applying density functional theory, the influence of dopants on the thermodynamic stability of these garnets was studied. Probable atomic configurations and their impact on materials’ properties were investigated with the focus on understanding the influence of these configurations on structural stability, phase preference, and ionic conductivity. In addition to the computational study, series of cubic-phase garnet compounds were synthesized and their electrochemical performance was evaluated experimentally. Our findings reveal that the stability of cubic phase in doped Li-garnets is primarily governed by enthalpy, with configurational entropy playing a secondary role. Moreover, we establish that the increased number of doping elements significantly enhances the cubic phase’s stability. This in-depth understanding of materials’ properties at atomic level establishes the basis for optimizing high-entropy ceramics, contributing significantly to the advancement of solid-state lithium batteries and other applications requiring innovative material solutions.